2001
DOI: 10.1074/jbc.m005626200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of CR6 (GADD45γ) with Proliferating Cell Nuclear Antigen Impedes Negative Growth Control

Abstract: GADD45, MyD118, and CR6 (also termed GADD45␣, ␤, and ␥) comprise a family of genes that encode for related proteins playing important roles in negative growth control, including growth suppression. Data accumulated suggest that MyD118/GADD45/CR6 serve similar but not identical functions along different apoptotic and growth suppressive pathways. It is also apparent that individual members of the MyD118/GADD45/CR6 family are differentially induced by a variety of genetic and environmental stress agents. The MyD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 47 publications
3
80
0
Order By: Relevance
“…Colony re-plating assays, which reflect proliferative capability of progenitor cells (Nakahata and Ogawa, 1982), have indicated prolonged proliferation capacity of gadd45a-deficient and gadd45b-deficient BM-derived CFU-GM progenitors. This may be indicative of the negative growth regulatory function of gadd45 proteins and their ability to interact with p21 (Vairapandi et al, 1996;Azam et al, 2001) to modulate this function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Colony re-plating assays, which reflect proliferative capability of progenitor cells (Nakahata and Ogawa, 1982), have indicated prolonged proliferation capacity of gadd45a-deficient and gadd45b-deficient BM-derived CFU-GM progenitors. This may be indicative of the negative growth regulatory function of gadd45 proteins and their ability to interact with p21 (Vairapandi et al, 1996;Azam et al, 2001) to modulate this function.…”
Section: Discussionmentioning
confidence: 99%
“…These observations raise the possibility that deficiency in either gadd45b or gadd45a alters the function of the hematopoietic stem cell compartment in response to physiological stress. In this regard, it will be of interest to assess the possible role of Gadd45 protein interaction with p21 (Vairapandi et al, 1996;Azam et al, 2001), which has been implicated in the regulation of hematopoietic stem cell quiescence and cell survival (Asada et al, 1999;Cheng et al, 2000;Marone et al, 2002). Inflammatory signals arising from IP administration of sodium caseinate, which is known to rapidly stimulate myelopoiesis in murine BM (Liebermann and HoffmanLiebermann, 1989), failed to stimulate myelopoiesis in gadd45aÀ/À and gadd45bÀ/À mice, impairing accumulation of myeloid cells in the peritoneum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCNA-Work conducted in our laboratory and in the laboratory of Dr. Albert Fornace (Georgetown University) has shown that all three Gadd45 proteins interact with PCNA (11,23,33), a nuclear protein that plays a central role in DNA repair and replication (38-39 & therein). It was suggested that interaction of Gadd45a with PCNA is involved in nucleotide excision repair (NER) of DNA (24).…”
Section: Gadd45 Mode Of Action: Interaction With Partner Proteinsmentioning
confidence: 99%
“…Recently, we have shown that both Gadd45b and Gadd45g also interact with the cdc2/cyclinB1 complex and inhibit cdc2 kinase activity following exposure of cell to genotoxic stress (2). p21-We have shown that all three Gadd45 proteins interact with the cyclin dependent kinase inhibitor p21 (11,33), a p53 target gene (45) implicated in G1/S (46-49) and G2/M (50) cell cycle arrest. The role of Gadd45 protein interactions with p21 is still unclear.…”
Section: Unpublished and 11)mentioning
confidence: 99%